Analysis of the Network, Staffing, and Activity of the Healthcare System and Cardiology Service of Kyiv Oblast - Ivaniuk, Anatolii V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Providing high-quality cardiac care for the population is impossible without a thorough analysis of the number of healthcare facilities that can provide such services, the distribution of cardiologists and cardiovascular surgeons per appropriate number of the population, and proper monitoring of specialized examinations required for patients seeking such care. The aim. Getting inside the scope of the network, staffing, and activities of the healthcare system and cardiology service of Kyiv oblast. Materials and methods. Data on mortality, morbidity of the population, the structure of healthcare institutions, and the performance of the network of healthcare facilities of Kyiv oblast were the material of the study. The general scientific approach, i.e. synthesis, generalization, interpretation, system analysis, and medical statistics, was used to attain the aim. Results. The absence of cardiologists was noted in some territorial units of Kyiv oblast, either entirely or at certain time intervals. At the same time, the supply of cardiovascular surgeons was also inadequate. The dynamics of the number of beds in the region showed negative trends from 2018 to 2021. The increase in the workload of cardiac surgeons had a steady upward trend during 2018-2021, along with a peak number of operations and a statisticallysignificant correlation with an increase in patient mortality. The number of specialized cardiology examinations carried out for the population in the region is also insufficient. Conclusions. The network, staffing and activities of the cardiology service of Kyiv oblast do not meet the needs of the population and require a systematic approach to provide reforms at the level of the regional leadership to solve the issue of optimizing cardiac care for the population, taking into account the formation of local communities.